Pengaruh Komunikasi Politik Melalui TikTok Terhadap Dukungan Gen Z pada Pemilu 2024 - Dewi, Nevy Rusmarina (JPW (Jurnal Politik Walisongo), 2024)
The 2024 election has passed, there are many surprises both in the process and in the final results. Prabowo-Gibran was finally declared the winner of the February 14 2024 election, despite the long process leading to its determination. It doesn't matter who the winner is, it's just that this election has given rise to new media in political campaigns and using mature strategies to get votes as expected. The aim of this research is to find out how Tik Tok has become a new and effective political communication medium in the process of conveying political messages. And how Generation Z and millennials as the main users of Tik Tok are influenced by the content in it, thereby influencing their political decisions in election participation. This research uses qualitative research methods with library studies. The results of this research reveal that Tik Tok is the main target of political campaigns because almost all of the young generation who are the main voters in elections use this application in their daily lives, giving rise to a strategy to attract the sympathy of the younger generation through uploaded interesting content. Apart from that, the younger generation is influenced by the content presented because it suits their movements and thinking patterns, so content that suits their lifestyle will influence their political decisions.